2012
DOI: 10.5923/j.ijpbs.20120205.06
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intimate Partners’ Violence on Unintended Pregnancy in Bangladesh

Abstract: Violence and unintended pregnancy are increasingly becoming essential public health issue in Bangladesh. The study aimed to examine the influence of vio lence on unintended pregnancy taking selected covariate into consideration. This study used nationally representative sample of the Bangladesh Health and Demographic Survey 2007 where data were obtained from 10,996 ever married wo men aged 10-49 years. Of them 4,925 wo men having their last birth in the last five years were selected for this study to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Around 20% reported that their last birth had resulted from an unintended pregnancy (Table 2). Unintended pregnancy was significantly higher among women who had experienced physical or sexual violence in India and Bangladesh, and the results are consistent with those of previous studies (Silverman et al, 2007;Stephenson & Koenig 2008;Raihana et al, 2012). However, in the case of Nepal this association was not significant, but this could have been due to small sample size.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Around 20% reported that their last birth had resulted from an unintended pregnancy (Table 2). Unintended pregnancy was significantly higher among women who had experienced physical or sexual violence in India and Bangladesh, and the results are consistent with those of previous studies (Silverman et al, 2007;Stephenson & Koenig 2008;Raihana et al, 2012). However, in the case of Nepal this association was not significant, but this could have been due to small sample size.…”
Section: Discussionsupporting
confidence: 90%
“…Women who ever used contraception were more likely to report unintended birth. Although some previous studies have suggested the use of contraception to be higher among women who reported unintended childbirth (Begum et al, 2010;Raihana et al, 2012;Shabnam & Mukherjee, 2013), the reasons for this are uncertain. In countries with moderate to high contraceptive prevalence, the majority of unintended or unplanned pregnancies are the result of either contraceptive discontinuation or contraceptive failure (Black et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Differences in sample characteristics (age and pregnancy status) might explain this result or it might indicate a mediating role of sexual violence on the association of educational status with unintended pregnancy. Previous studies from Colombia and Bangladesh also found insignificant positive association between education and risk of unintended pregnancy [34]. Educated women may be more likely to reject traditional gender norms and may try to retaliate to their husband’s sexual violence which may have led to further revenge from husbands in a male dominated society [10].…”
Section: Discussionmentioning
confidence: 99%
“…Educated women may be more likely to report any kind of sexual violence and unintended pregnancy than women with less/no education [6]. Whereas, non-educated women might normalize sexual violence in marital relationship than their educated counterparts, which might have led to under-reporting of sexual violence and unintended pregnancy [34]. Despite these findings, importance of women’s education for positive health outcomes remains undisputed.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies from South Asian countries like Pakistan and Bangladesh have reiterated that sexual IPV influences mistimed and unwanted pregnancies [18][19][20]. The differences in the prevalence of unwanted pregnancies could be partly due to inclusion criteria and sample size variations between the studies.…”
Section: Discussionmentioning
confidence: 99%